An improved routing algorithm in communication network based on cloud computing technology. (2018) - Xiang, Shuaiqiu; Cheng, Dongsheng; Zhu, Zhenjia
This paper proposed a research of communication network routing algorithm based on cloud computing technology. Our research designed cloud computing platform which applies to big data through the introduction of different types of routing protocols. The optimal routing selection of communication network and node energy balanced load provided the data storage and computing environment. In the route optimisation stage, this research used pheromone anycast mechanism for selecting route on the basis of the importance of heuristic factor on the path and the residual pheromone, avoiding the algorithm fall into local optimum. Taking the energy consumption of nodes as weight for the routing updates and adjustment in nodes-cluster, we controlled the energy consumption of inter-nodes at the optimal level. Simulation results show that in 20%–70% of the maximum traffic, the node energy consumption of routing algorithm in paper is better than the traditional algorithm, the proposed communication network routing algorithm has low average error rate of network data, high link reliability and good energy saving effect.